Diagnosis and surgical treatment of obstructed hemivagina and ipsilateral renal anomaly in a dog: a case report - Choo, Younwoo; Cho, Jun-Sik; Cha, Ah-Young; Kim, Hwi-Yool; Kim, Jung-Moon (Frontiers in Veterinary Science, 2024)
Obstructed hemivagina and ipsilateral renal agenesis (OHVIRA), also called Herlyn–Werner–Wunderlich syndrome, is an extremely rare Müllerian duct anomaly accompanied by Wolffian duct anomalies. A 10-year-old intact female Yorkshire Terrier weighing 3.35 kg was presented with anorexia, depression, vomiting, and abdominal pain. Radiography, ultrasonography, and computed tomography revealed uterine didelphys, obstructed hemivagina, a cystic structure around the right uterus, and right renal agenesis, leading to the diagnosis of OHVIRA syndrome. An ovariohysterectomy and decompression of the obstructed right hemivagina were performed, and the cystic structure near the right uterine horn was removed by en bloc resection, along with the right uterus and ovary. After the surgical intervention, the patient’s symptoms including abdominal pain, anorexia, and depression were immediately resolved. The patient was followed up for 1 month postoperatively with ultrasonography at 2-week intervals, which revealed the progression of mild fluid retention in the right hemivagina. However, no additional urogenital findings were identified, and the patient continued to exhibit no overt clinical symptoms. This case report describes the diagnosis and surgical treatment of the first documented case of OHVIRA syndrome in an animal. Unlike in human medicine, where vaginal septectomy is performed to prevent dilatation of the obstructed hemivagina and thereby resolve clinical symptoms, performing ovariohysterectomy combined with fluid aspiration from the obstructed hemivagina showed a favorable postoperative prognosis in the dog.